Exponentiauy Type Pseudo Almost Automorphic Mild Solution for a Class of Linear Differential Equation - YAO Huili; GUO Mingjun; WNG Jingnan; SONG Xiaoqiu (Journal of Harbin University of Science and Technology)
Differential equations are a kind of mathematical models which have been established to solve all kinds of practical problems The existence problems of various solutions for differential equations are a main research direction Pseudo almost automorphic functions are more wide functions than almost automorphic functions and asymptotically almost automorphic functionsThe applications of exponentiauy type pseudo almost automorphic f unctions on a class of linear differential equations will be investigated, the existence problems and uniqueness problems of exponentiauy type pseudo almost automorphic mild solution of this type equations are researched by using some related theories of C0 semigroup and this type i functions in this paper